(3MGTjI JgPjH GdefWb (B( (3GdOhGfi (B)s - (3edG YHO Gddgs; (3LdGd GdOjf eMeO Hf CSYO GdUOjbj GdOhGfj, GdOhGfj,J (B918 (3g` s
(3ChdgG (B:s
(3ddg GdMeO hGdUdGI Ydi YHGOg GdPjf GUWai agPg cdeGJ eJYdbI HJMbjb eHMK GdehVhY ef MGTjI efWb GdJgPjH s
(3BNQgG (B:s
(3hSdWI GdOdh Cda SfI hSdWI GdMhJ Gda SfI Je s
(3JgPjH GdefWb ddJaJGRGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B32s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B- (3cdjI Mbhb (B(112 - (3H(B) s
Keywords: (3GdadSaI hGdefWbs